2017
DOI: 10.1098/rsos.171201
|View full text |Cite
|
Sign up to set email alerts
|

13 C and 15 N assimilation and organic matter translocation by the endolithic community in the massive coral Porites lutea

Abstract: Corals evolved by establishing symbiotic relationships with various microorganisms (the zooxanthellae, filamentous algae, cyanobacteria, bacteria, archaea, fungi and viruses), forming the ‘coral holobiont'. Among them, the endolithic community is the least studied. Its main function was considered to be translocation of photo-assimilates to the coral host, particularly during bleaching. Here, we hypothesize that (i) endolithic algae may show similar primary production rates in healthy or bleached corals by cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 40 publications
(65 reference statements)
4
61
0
Order By: Relevance
“…All together, DDN may help O. patagonica to overcome C limitation, thereby possibly contributing to its high recovery potential from annual bleaching events. Sangsawang and colleagues () also observed a fourfold increased DDN assimilation into the tissue of bleached P. lutea corals, whereas assimilation by endoliths was similar in bleached and non‐bleached corals. However, they identified that part of the tissue‐assimilated DDN was fixed and translocated from the endolithic compartment, and similarly, translocation of DDN between the individual compartments may have occurred in the present study.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…All together, DDN may help O. patagonica to overcome C limitation, thereby possibly contributing to its high recovery potential from annual bleaching events. Sangsawang and colleagues () also observed a fourfold increased DDN assimilation into the tissue of bleached P. lutea corals, whereas assimilation by endoliths was similar in bleached and non‐bleached corals. However, they identified that part of the tissue‐assimilated DDN was fixed and translocated from the endolithic compartment, and similarly, translocation of DDN between the individual compartments may have occurred in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…Thereof, the majority was detected within the host tissue (62%) and endoliths (33%), with only a minor proportion present in Symbiodinium (7%) and mucus (0%). Previous 15 N 2 tracer studies on tropical corals reported similar DDN assimilation rates into the tissue compartment of S. pistillata (0.97–3.58 ng N cm −2 h −1 ; Bednarz et al ., ) and Porites lutea (2.47 ± 0.78 ng N cm −2 h −1 ; Sangsawang et al ., ). Although two other studies on S. pistillata traced >95% of DDN within Symbiodinium and suggested this compartment as the primary site for DDN (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations